When Zaydeh danced on Eldridge Street - Rael, Elsa (Simon & Schuster Books for Young Readers, 1997)
While staying with her grandparents in New York City in the mid-1930s, eight-year-old Zeesie joins in the celebration of Simchat Torah and sees a different side of her stern grandfather.